Dendrochronological studies in North Africa: reality and prospects - Farahat, Emad; Gärtner, Holger (Frontiers in Ecology and Evolution, 2024)
The southern Mediterranean region, particularly North Africa, is a crucial area for biodiversity conservation. However, the impacts of climate change on plant species in this region are not well understood. Dendroecology, the study of tree rings, is a valuable technique for analyzing the effects of environmental changes on woody plants over time. In this study, we intend to assess the state of the art in dendrochronological research in North Africa and identify knowledge gaps and limitations in the field. The period of analysis spans from 1979 to 2023. We used all the available literature in Dendrobox and Google Scholar during this period. Our study revealed several research gaps in the region, including the need for more studies on the history of forest fires and their relationship to climate conditions in Morocco, Algeria, and Tunisia, the impact of climate on the anatomical characteristics of growth rings, and the effects of climate change on tree species diversity and forest health. Applying this technique in the future would allow for detailed insights into the effect of climate on the internal structure and growth of forest trees. The findings of this study will help guide future research and contribute to a better understanding of the climate-growth relationship of woody plants in North Africa.